Studi Analisis Kesalahan Konsep dalam Buku Kalkulus Multivariabel dan Implikasinya Terhadap Pendidikan Matematika - Suwanto; Pujiono Sihite; Nurul Azmira Pane; Venesya Pitta Rezeki Siburian; Joyce Lidia Patricia Daeli; Mukhtar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The precise definition and presentation of concepts play a crucial role in students’ understanding of advanced mathematics. This study aims to analyze the alignment of the content in the Multivariable Calculus textbook with mathematically correct concepts and to identify sections that may lead to misconceptions. The method employed is a qualitative-descriptive analysis through content analysis, focusing on definitions, explanations, and example problems presented in the Multivariable Calculus textbook under study. The analysis results indicate several inaccuracies in the presentation, such as inconsistent use of symbols and unclear explanations of concepts. These inaccuracies have the potential to hinder students’ conceptual understanding. This study recommends a thorough review of the content in the Multivariable Calculus textbook to ensure conformity with mathematical principles and to support the learning process.